Image Denoising Using Fourth Order Wiener Filter with Wavelet Quadtree Decomposition - Issam Dagher; Catherine Taleb (Journal of Electrical and Computer Engineering)
Visual information transmitted in the form of digital images is becoming a major method of communication in the modern age, but the image obtained after transmission is often corrupted with noise. The received image needs processing before it can be used in applications. Image denoising involves the manipulation of the image data to produce a visually high quality image. This paper uses the fourth order nonlinear wiener filter with wavelet quadtree decomposition and median absolute deviation. It will be shown that this new algorithm is comparable to other algorithms like BM3D, LPG-PCA, and KSVD.